The epidemiology of injuries in English youth community rugby union. Issue 15 (19th October 2010) - Haseler, Christine M; Carmont, Michael R; England, Michael
Abstract : Introduction: Recent studies report the incidence and epidemiology of injury in professional rugby union; however, there is limited research in amateur and youth rugby. Injuries in youth rugby may have consequences for sports participation and physical development. The authors performed a prospective cohort study of injuries during youth community rugby. Methods: An injury surveillance programme was established for the 2008–2009 season (9 months, 1636 player-hours) of an English community rugby club. The study included 210 players, all males, in Under 9 to Under 17 (U9–U17) age groups. These were categorised into mini, junior, pubertal and school participation age groupings. Injuries were defined according to the International Rugby Board consensus statements. Results: There were 39 injuries reported (overall injury rate 24/1000 player-hours). Injury rates ranged from 0 to 49.3/1000 player-hours. More injuries occurred in junior (34.2/1000 player-hours) than in minis (11.9/1000 player-hours) (p<0.025). Higher numbers of moderate (20.6/1000 player-hours, p<0.005) and severe (9.5/1000 player-hours, p<0.05) injuries occurred in the U16–U17 age groups compared with younger age groups (U9–U10) where only minor injuries were reported. Most injuries occurred in the tackle (59%). The knee (4.9/1000 player-hours), shoulder (4.9/1000 player-hours) and head (4.3/1000 player-hours) were the most commonly affected areas. Concussion (1.8/1000 player-hours) affected half of the head injuries. Conclusions: Injuries in youth rugby occur infrequently and are lower than in adult series. The risk of injury and severity of injury increases with age. This study highlights the need for further research into injury risk factors around puberty and the need for first aid provision.